Baseline Plasma Fibrinogen and Glycated Haemoglobin (HbA1c) Levels in Normoglycaemic Offspring of Adults with Type 2 Diabetes Mellitus - EO Taiwo; LO Thanni; OP Taiwo (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: Type 2 Diabetes mellitus (T2DM) is known to be preceded by a long pre-diabetic stage. Family studies have confirmed that the incidence of T2DM in the first-degree offspring of T2DM patients is higher than in the non-diabetic population. The levels of plasma fibrinogen and HbA1c in offspring of T2DM patients may be markers of the development of T2DM later in life. Objectives: To determine the plasma fibrinogen and HbA1c levels of normoglycaemic offspring of T2DM patients. Methods: This study involved randomly selected 100 offspring of T2DM patients (ODP) and 100 offspring of non-diabetic parents (ONDP) aged between 16 and 40 years. Fasting Blood Glucose (FBG), plasma fibrinogen and HbA1c and height and body weight were measured using standard methods. Results: The mean age of the ODP and ONDP were similar: 23.3±0.44 years and 23.44 ±0.40 years, respectively. The mean BMI was 23.83±0.42kg/m2 for ODP and 23.20±0.29kg/m2 for ONDP. The prevalence of overweight was 13.0% and 25.0% among the ODP and ONDP, respectively. The mean plasma fibrinogen was significantly higher in ODP (322.85 ± 5.15g/l vs 303.11 ±4.92 g/l; p = 0.006). The mean plasma HbA1c was also significantly higher among OND (5.13±0.03% vs 4.76±0.05; p = 0.000). Conclusions: The plasma fibrinogen and HbA1c levels are higher among ODP than ONDP. This pattern of variations may serve as a reason for instituting precautionary measures since it predates the development of T2DM.